A systematic review and meta-analysis of the association between sugar intake and dental caries in Nigeria - Folahanmi Tomiwa Akinsolu; Titilola Abike Gbaja-Biamila; Abideen Olurotimi Salako; Ifeoluwa Eunice Adewole; Mobolaji Timothy Olagunju; Olunike Rebecca Abodunrin; Oluwabukola Mary Ola; Chukwuemeka Abel; George Uchenna Eleje; Oliver Chukwujekwu Ezechi; Maha El Tantawi; Joanne Lusher; et al. (BMC Oral Health)
Abstract Background There is no national data on the association between sugar intake and caries experience in Nigeria. This systematic review and meta-analysis aimed to assess the association between sugar intake and caries experience in Nigeria. Methods A search was conducted across the PubMed, Web of Science, Scopus, and Embase databases for articles published between January 2001 and March 2023 on the associations between sugar consumption and caries experience. This systematic review and meta-analysis were registered with PROSPERO (CRD42022372689). Data extracted included details of the study design, sample size, age and gender of study participants, and regions/states in Nigeria where the study was conducted. In addition, the types of sugary foods/beverages consumed, frequency and quantity of sugar intake, and periods of high sugar consumption were extracted. The studies’ bias risks were also assessed. Results The review included 14 cross-sectional studies conducted between 2007 and 2023. Twelve (85.7%) studies were conducted in Southwest Nigeria. Seven (50.0%) had study participants with primary dentition, while eight (57.1%) had study participants with permanent dentition. The odds of caries are 18% higher in the group that consumes sugar compared to the group with low sugar intake (OR = 1.18, 95% CI: 0.87, 1.59). The odds of caries in primary (OR = 1.13, 95% CI: 0.23, 5.44) and permanent (OR = 1.15, 95% CI: 0.88, 1.52) dentition were higher in the group that consumes sugar compared to the group with low sugar intake. There were no statistical associations between sugar consumption and caries experience. Of the 14 included studies, thirteen (92.8%) were classified as “low risk.” Conclusion Although a high frequency of sugar intake increased the risk of dental caries, this association did not reach statistical significance in Nigeria’s primary and permanent dentitions. Future studies should include longitudinal studies and studies that assess differences in the measures for sugar consumption and its association with the risk of caries.